Contamination of Zearalenone from China in 2019 by a Visual and Digitized Immunochromatographic Assay - Xia Hong; Yuhao Mao; Chuqin Yang; Zhenjiang Liu; Ming Li; Daolin Du (Toxins, 2020)
Zearalenone (ZEN) is a prevalent mycotoxin that needs intensive monitoring. A semi-quantitative and quantitative immunochromatographic assay (ICA) was assembled for investigating ZEN contamination in 187 samples of cereal and their products from China in 2019. The semi-quantitative detection model had a limit of detection (LOD) of 0.50 ng/mL with visual judgment and could be completely inhibited within 5 min at 3.0 ng/mL ZEN. The quantitative detection model had a lower LOD of 0.25 ng/mL, and ZEN could be accurately and digitally detected from 0.25–4.0 ng/mL. The ICA method had a high sensitivity, specificity, and accuracy for on-site ZEN detection. For investigation of the authentic samples, the ZEN-positive rate was 62.6%, and the ZEN-positive levels ranged from 2.7 to 867.0 ng/g, with an average ZEN-positive level being 85.0 ng/g. Of the ZEN-positive samples, 6.0% exceeded the values of the limit levels. The ZEN-positive samples were confirmed to be highly correlated using LC-MS/MS (R2 = 0.9794). This study could provide an efficiency and accuracy approach for ZEN in order to achieve visual and digitized on-site investigation. This significant information about the ZEN contamination levels might contribute to monitoring mycotoxin occurrence and for ensuring food safety.